Peta Fiqh Mu'āṣir Muslim Progresif - iffah Muzammil (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2012)
Many contemporary Muslim scholars argue that Islamic jurisprudence (fiqh) is not ready to face the demands of the modern era. Modernity is so powerful that it weakens the foundation of fiqh on the one hand, and opens up new opportunities that cannot be reached by fiqh on the other. The method that fiqh has introduced is in itself incapable of adapting to new situation and also incapable of addressing new issues such as the issue of human right, constitusionalism, and the like. It is in this context that contemporary Muslim scholars speak out for reform in the methodology of fiqh as well the application of this methodology in addressing new issues. This paper is concerned with discussing this problem by referring to the thought of some leading authority in this regard such as Abdullahi Ahmed an-Naim, Aboe el-Fadl, and Nasr Hamid Abū Zayd. The paper argues that for these scholars, fiqh has lost its role and power in the modern society because of its discriminative trait. Fiqh must therefore deal with this negative image if it is to restore its influence in the modern civilization.